Awareness, understanding, and help seeking for behaviour problems by parents of primary school age children in Central Jakarta: A qualitative study - Tjhin Wiguna; Myron L. Belfer (Indonesian Pediatric Society Publishing House, 2010)
Background Understanding children's behaviour and emotional conditions will allow parents to help them cope with the tasks of growing up. The accuracy of parents to identify their children as needing mental health services, and the factor that might influence parental perceptions is important. Objectives To explore parents' recognition and help-seeking patterns for behavior and emotional problems of school age children; To identify parents' perceived needs and barriers in achieving access to appropriate mental health services. Methods We involved six parents who had primary school children with behavior and/or emotional problems identified by their class teacher. Parents were interviewed by using a semistructured clinical interview, some were adapted from the Arthur Kleinman's explanatory model of illness. Data were presented in descriptive and interpretative accounts. Results In general, parents were aware that their children had behavioural and emotional problems but assumed it was part of their normal development. Four parents did not take their children to seek any professional help, assuming they would be able to overcome this situation with the helping hand from the school class teachers. Parents perceived that they were weak in parenting their child. Conclusion This study emphasizes the need to increase parents' awareness and understanding and helping agencies so they can recognize the problems accurately and overcome the barriers appropriately. [Paediatr Indones. 2010;50:18-25].